Successful treatment of recalcitrant generalized pustular psoriasis in a young child with interleukin-36 receptor antagonist mutation with secukinumab monotherapy - Henrietta Albela; Sabeera Begum; Kin Fon Leong (Wolters Kluwer Medknow Publications, 2021)
Generalized pustular psoriasis (GPP) is a severe, life-threatening form of psoriasis. Deficiency of interleukin (IL)-36 receptor antagonist has been found in a subset of patients with GPP, which is usually more difficult to treat with conventional treatment. We report a case of a 4-year-old Malaysian-Chinese boy with GPP and homozygous mutation at c.115+6T>C within the interleukin-36 receptor antagonist (IL36RN) gene, who was treated successfully with off-label use of secukinumab monotherapy after failure of treatment with acitretin and cyclosporine A.